Procedural Problems in Indonesia's Treaty-Making Process: A Comparative Analysis - AWJ, Fransiskus (Universitas Muhammadiyah Yogyakarta, 2021)
This article discusses several procedural problems in Indonesia’s rules on ratifying treaties. These problems stem from gaps in the existing laws as well as conflict between the general law on ratification and the more specific law that regulates ratification of trade treaties. The problems involve timing and inconsistency within the practice of treaty-ratification and its product. The issue of timing concerns the time that it takes to ratify a treaty. The issue of practice concerns inconsistency within the treaty-ratification practice because of a lack of procedures and the strange existence of procedures for specific treaties without the existence of general ones. The issue of product concerns an inconsistency within the result of ratifying a treaty. The problems are analyzed by observing the laws and practices of treaty-ratification of other states.